Developing environmental management system (EMS) based on ISO 14001 / Tewelde Gebre; Belay Abera - Gebre, Tewelde
Environmental Management System (EMS) is the most important and finest approach to deal with company’s environmental concerns by emphasizing on incorporating environmental goals and priorities into a company’s routine operations. EMS is being implemented in many more companies to avoid, reduce and control the adverse environmental impacts of its activities, achieve compliance with applicable legal and other requirements to which the organization subscribes to and assist in continually improving environmental performance. ISO 14001 is a standard that specifies the requirements for an EMS that an organization can use to enhance its environmental performance. Many companies have chosen to obtain independent certification of their EMS to the international standard ISO 14001. This training manual on ISO 14001 EMS is designed to be of assistance in the environmental performance of Manufacturing Industries.